Open distal anastomosis in the frozen elephant trunk technique: initial experiences and preliminary results of arch zone 2 versus arch zone 3. (1st April 2019) - Leone, Alessandro; Di Marco, Luca; Coppola, Giuditta; Amodio, Ciro; Berardi, Marianna; Mariani, Carlo; Votano, Daniela; Bacchi Reggiani, Maria Letizia; Di Bartolomeo, Roberto; Pacini, Davide
Abstract: OBJECTIVES: We compared the results of 2 groups of patients who underwent aortic arch replacement with the frozen elephant trunk technique. In the first group, the distal anastomosis was performed in arch zone 2; in the second control group, the distal anastomosis was performed in arch zone 3. METHODS: Between January 2007 and April 2018, the frozen elephant trunk technique was used in 282 patients. The median age was 62 years (range 18–83 years), and 233 patients were men (82.6%). Two different frozen elephant trunk prostheses were used: the Jotec E-vita open prosthesis in 167 patients (59.2%) and the Vascutek Thoraflex hybrid prosthesis in 115 patients (40.8%). Patients were divided into 2 groups according to the distal anastomosis site: zone 2 group (69 patients) and zone 3 group (213 patients). The main indications were chronic aortic dissection ( n  = 164, 58.2%), degenerative aneurysm ( n  = 72, 25.5%) and acute aortic dissections ( n  = 45, 16%). RESULTS: The overall in-hospital mortality rate was 17%: 20% for the zone 2 group and 16% for the zone 3 group, without significant differences, also in terms of cardiopulmonary bypass and myocardial ischaemia times. However, the visceral ischaemia time was significantly shorter for the zone 2 group, whereas the antegrade selective cerebral perfusion time was significantly longer for the same group. Recurrent laryngeal nerve injury rate was lower in the zone 2 group. The overall postoperative paraplegia rate was 3.5%, whereas the occurrence of permanent neurological dysfunction and dialysis was 9% and 19%, respectively, with no significant differences between the groups. CONCLUSIONS: 'Proximalization' of the distal anastomosis can be used for arch reconstruction, especially in complex cases such as reoperations or acute aortic dissections. Furthermore, with the aid of branched hybrid grafts, a reduction of the visceral ischaemia time is achieved.